2019
DOI: 10.1111/jth.14613
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulant for the prevention of thrombosis in ambulatory patients with cancer: A systematic review and meta‐analysis

Abstract: Background It is unclear if direct oral anticoagulant (DOAC) is efficacious and safe for prophylaxis of venous thromboembolism (VTE) in ambulatory patients with cancer. Methods We performed a systematic review using EMBASE, MEDLINE, and CENTRAL. Inclusion criteria included adult ambulatory patients with cancer, prophylactic use of DOAC, and randomized controlled trials. Exclusion criteria included pediatric patients, inpatient or postoperative setting, therapeutic indication of DOAC, or non‐phase III randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 44 publications
(66 reference statements)
1
43
0
1
Order By: Relevance
“…Considered together, these trials showed a significant benefit of the oral anticoagulants for the prevention of VTE with an acceptable incidence of major bleeding. Recently, at least two meta-analyses have assessed the role of DOACs in this setting [36,48]. Beccatini et al [36] included three randomized clinical trials and describe a significant reduction of VTE with DOACs [odds ratio (OR) 0.49; 95% CI 0.33-0.74].…”
Section: Prophylaxis Of Vte In Ambulatory Cancer Patients During Systmentioning
confidence: 99%
“…Considered together, these trials showed a significant benefit of the oral anticoagulants for the prevention of VTE with an acceptable incidence of major bleeding. Recently, at least two meta-analyses have assessed the role of DOACs in this setting [36,48]. Beccatini et al [36] included three randomized clinical trials and describe a significant reduction of VTE with DOACs [odds ratio (OR) 0.49; 95% CI 0.33-0.74].…”
Section: Prophylaxis Of Vte In Ambulatory Cancer Patients During Systmentioning
confidence: 99%
“…A similar pattern of clinical outcomes was observed over 6 months and over 5 years (see Supporting Table 5). The absolute differences in all clinical outcomes, including overall VTE, PE, DVT, MB, CRNMB, and mortality, were all within the 95% CI of previously reported outcomes from the meta‐analysis at 6 months . Minor variations in outcomes were likely driven by the inclusion of a drug nonadherence/discontinuation factor in the Markov model, which led to small attenuations of the absolute risk reductions of the primary outcomes.…”
Section: Resultsmentioning
confidence: 59%
“…Subgroup meta-analyses were performed for patients with Khorana scores ≥3 and 2 after outcomes were obtained directly from the trial authors. 13 Because of the low case fatality associated with PE, MB, and ICH, pooled estimates were derived from 2 prophylaxis trials and 1 treatment trial (Hokusai-VTE Cancer). 15…”
Section: Model Input: Measurement Of Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A pooled analysis of the two studies has nevertheless been performed and showed a 6-month VTE risk reduction of 0.56 (95%CI 0.35-0.89) on DOACs, with a non-significant increase in major bleeding (1.96; 95%CI 0.80-4.82) [53]. In terms of absolute difference, this corresponded to a VTE risk reduction of 4% (95%CI 0.01-0.07, NNT 25) at the cost of a 1% (95%CI 0.0-0.02) increase (albeit statistically non-significant) in major bleeding (NNH 100).…”
Section: Use Of Doac For Vte Preventionmentioning
confidence: 99%